2017
DOI: 10.3892/ijmm.2017.3232
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of long non-coding RNA MALAT1 in lipopolysaccharide-induced acute kidney injury is mediated by the miR-146a/NF-κB signaling pathway

Abstract: The present study aimed to examine the expression and function of the metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/microRNA (miR)-146a/nuclear factor (NF)-κB axis in lipopolysaccharide (LPS)-induced acute kidney injury (AKI). The mRNA levels of MALAT1 and miR-146a in AKI tissues and cells were detected using reverse transcription-quantitative polymerase chain reaction analysis. The NF-κB pathway proteins and cell viability were assessed using western blot analysis and the MTT method, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 37 publications
2
62
1
Order By: Relevance
“…[ 29,30 ] One research represented that lncRNA MALAT1 knockdown could mollify LPS‐engendered AKI via the mediation of miR‐146a. [ 31 ] Other research showed that NEAT1 repression could allay sepsis‐evoked AKI via targeting miR‐204. [ 32 ] MiR‐106b‐5p is a mature form of miR‐106b, which is encoded by the miR‐106b‐25 cluster in the long arm 21 regions of human chromosome 7 (7q21).…”
Section: Discussionmentioning
confidence: 99%
“…[ 29,30 ] One research represented that lncRNA MALAT1 knockdown could mollify LPS‐engendered AKI via the mediation of miR‐146a. [ 31 ] Other research showed that NEAT1 repression could allay sepsis‐evoked AKI via targeting miR‐204. [ 32 ] MiR‐106b‐5p is a mature form of miR‐106b, which is encoded by the miR‐106b‐25 cluster in the long arm 21 regions of human chromosome 7 (7q21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulation of NEAT1 negatively regulates miR‐204 and activates NF‐κB pathway, thereby serves as an important diagnostic marker and therapeutic target in sepsis‐induced AKI patients (Chen et al, ). In addition, MALAT1 and Maternally expressed gene 3 (MEG3) promotes LPS‐induced AKI by modulating miR‐146a/NF‐κB axis and miR‐21/PDCD4 pathways, respectively (Ding et al, ; R. Yang et al, ). Arid2‐IR is a newly identified proinflammatory lncRNA in kidney disease.…”
Section: Role Of Lncrnas In Akimentioning
confidence: 99%
“…It is suggested that after binding to a specific protein, MALAT1 can shuttle between the cytoplasm and the nucleus to alter the intracellular localization of the protein. MiR-129-5p Growth and metastasis of triple-negative breast cell↑ Zuo, Li, Zhou, Ma, and Fu (2017) MiR-142-3p and miR-129-5p HMGB1 Growth of osteosarcoma cell↑ MiR-129-5p HMGB1 Proliferation of colon cancer↑ Jie and Zhao (2017) MiR-133 Srf Differentiation of myocyte↑ Han, Yang Cao, and Liang (2015) MiR-140 Slug and ADAM10 Growth and invasion of uveal melanoma cell↑ MiR-140 NFYA Blood-tumor barrier permeability↓ Ma et al (2016) MiR-143-3p ZEB1 Growth and invasion of hepatocellular carcinoma cell↑ MiR-144-3p ROCK1 and ROCK2 Metastasis and proliferation of osteosarcoma cell↑ MiR-145 TGFBR2 and SMAD3 TGF-β1-induced EMT↑ Xiang, Zhang, Tang, and Li (2017) MiR-145 Bnip3 Cardioprotective effects↑ Zhao et al (2016) MiR-146b-5p TRAF6 Growth and metastasis of hepatocellular carcinoma cell↑ MiR-146a LPS-induced acute kidney injury↑ Ding et al (2018) MiR-155 FBXW7 Cell viability in glioma cell↓ Cao et al (2016) MiR-183 ITGB1 Cell growth in melanoma cell↑ Sun, Qin et al (2016) MiR-195 EGFR Growth and metastasis of hepatocellular carcinoma cell↑ MiR-200c ZEB1 and ZEB2 Endometriosis↑…”
Section: Malat1 Assists Protein Localizationmentioning
confidence: 99%